DISCOURSE ANALYSIS OF COHESIVE DEVICES IN STUDENT’S WRITING - Epi Siasi (STKIP PGRI Lubuklinggau, 2018)
This research attempts to analyze a piece of writing written by students of STKIP PGRI Lubuklinggau which was problematic in term of cohesion. This research was conducted in form of written discourse analysis. The data of the research was student’s writing and it was analyzed based on the work of Halliday and Hasan (1976). The student’s writing quality is discussed according to the problems by lack of cohesion devices. The student tend to use only a limited range of the many cohesive devices available, her texts appears to be difficult to understand because even the few cohesive devices they utilized were inaccurately used. This phenomenon not only creates disorganized texts but also renders the content incomprehensible to the reader. In conclusion, this research has shown that the student got difficulty in using the cohesive devices and it is needed of attention from the lecturers to give the overall cohesiveness as well in order to increase the quality of student’s writing.